2016
DOI: 10.2514/1.b36049
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Shedding Influence on Hybrid Rocket Pressure Oscillations and Combustion Efficiency

Abstract: Numerical simulation is performed and compared with a firing test of an H 2 O 2 ∕polyethylene hybrid rocket engine equipped with a catalyzer. The simulation is performed assuming an axisymmetric flow, unsteady Reynolds-averaged Navier-Stokes equations are solved based on a single-phase flow. Stable pressure oscillations are observed during the firing test and could be explained by the simulation with the formation of large-scale vortices at the end of the fuel grain and in the postcombustion chamber. These vor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Their studies were mainly focused on the formation of the large-scale vortices in the post-combustion chamber and its influence on small-scale vortices formed near the fuel surface as a result of the cross-flow of fuel and axially convicted product gases. Messineo et al [38] further studied the frequency shifts and jumps of hydrodynamic instabilities provoked by the vortex shedding in a hybrid rocket motor. French research group ONERA reported that the use of protrusions or diaphragms can significantly suppress combustion instabilities [12].…”
Section: Aim Of Investigationmentioning
confidence: 99%
“…Their studies were mainly focused on the formation of the large-scale vortices in the post-combustion chamber and its influence on small-scale vortices formed near the fuel surface as a result of the cross-flow of fuel and axially convicted product gases. Messineo et al [38] further studied the frequency shifts and jumps of hydrodynamic instabilities provoked by the vortex shedding in a hybrid rocket motor. French research group ONERA reported that the use of protrusions or diaphragms can significantly suppress combustion instabilities [12].…”
Section: Aim Of Investigationmentioning
confidence: 99%
“…In fact, when the pyrolysis reaction rates were obtained from thermogravimetric analyses, they were expressed in terms of reaction speeds with a pre-exponential factor A in sec −1 , while the pre-exponential constant A of Equation (16) was expressed in m/s and was obtained from curve fitting of surface regression experiments. When the form of Equation 14was used, a pre-exponential termÂ, which varied with temperature, could be computed from the pre-exponential factor, the fuel thermal diffusivity, and the non-dimensional regression rate from Equation (15). Tables 5 and 6 list the activation energy and the pre-exponential constant (see Table 5) or the pre-exponential factor (see Table 6) for the different HDPE pyrolysis laws.…”
Section: Sensitivity Analysis Of the Pyrolysis Modelmentioning
confidence: 99%
“…Indeed, the extension of those models to new motors that can be different in geometry, scale, etc., is hardly possible without the availability of existing experimental data for each motor. For these reasons, there is a renewed interest in the development of more accurate and advanced models based on Computational Fluid Dynamics (CFD) [3][4][5][6][7][8][9][10][11][12][13][14][15] that are capable of representing more accurately the physico-chemical phenomena involved. The numerical modeling of the fluid dynamics and the combustion process in the fuel port area and nozzle of a hybrid rocket is a challenging task as it involves strongly-interacting multiphysics processes such as fluid dynamics, fuel pyrolysis [16,17], atomization and vaporization of the oxidizer, mixing and combustion in the gas phase [11][12][13]18], thermochemical erosion of the nozzle [3,19], particulate formation, and the radiative characteristics of the flame.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations